PENYULUHAN ALUR PENDAFTARAN ONLINE PASIEN BPJS DI UPT PUSKESMAS KUBANG JAYA - Anastasya Shinta Yuliana; Alfitri Yana Yunita; Dea Ariesta Putri (LPPM Universitas Awal Bros, 2023)
Indonesian people are currently required to become participants in health insurance managed by BPJS, including foreigners who have worked for at least six months in Indonesia and have paid contributions. Then the Social Security Administering Body (BPJS) is a legal entity formed to administer health insurance programs. To make it easier for patients to seek treatment, there is online registration so that patients seeking treatment no longer need to queue. However, the public's lack of understanding of the online BPJS registration process means that people are not interested in using BPJS when seeking treatment and prefer to seek treatment at paid doctor's clinics. Counseling on the Online Registration Flow for BPJS Patients at the Kubang Jaya Community Health Center UPT is a very beneficial activity for Kubang Jaya Community Health Center Patients and Medical Staff, where with this counseling it is hoped that patients will not have to wait long in the registration process for treatment at the Puskesmas because they have registered online first. . And also help ease the workload of Kubang Jaya Health Center Medical Personnel. Then, I also hope that later by holding this outreach, patients can also implement it with their closest relatives regarding online BPJS registration.